2019
DOI: 10.1111/prd.12264
|View full text |Cite
|
Sign up to set email alerts
|

The mouth in inflammatory bowel disease and aspects of orofacial granulomatosis

Abstract: Inflammatory bowel disease has a wide range of possible oral manifestations, many of which overlap with those seen in other conditions, including orofacial granulomatosis. The precise etiology remains unclear, as is the exact relationship between orofacial granulomatosis and Crohn's disease. Overall, there is growing evidence that orofacial granulomatosis and oral Crohn's disease are distinct clinical disorders with optimal management requiring a multidisciplinary approach with input from appropriate specialis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0
12

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 122 publications
2
11
0
12
Order By: Relevance
“…Crohn's disease is a systemic inflammatory condition that most commonly affects the small bowel and colon, typically presenting with abdominal pain, diarrhea, weight loss, and poor appetite 1 . Additionally, Crohn's disease can have various oral findings including cobblestoning of mucosa, mucosal tags, deep linear ulcerations, and labial swelling 2 . Clinically, labial enlargement during the early course of the disease can occur as recurrent episodes lasting a few days or weeks, which over time, becomes persistently firm and indurated 3 .…”
Section: Discussionmentioning
confidence: 99%
“…Crohn's disease is a systemic inflammatory condition that most commonly affects the small bowel and colon, typically presenting with abdominal pain, diarrhea, weight loss, and poor appetite 1 . Additionally, Crohn's disease can have various oral findings including cobblestoning of mucosa, mucosal tags, deep linear ulcerations, and labial swelling 2 . Clinically, labial enlargement during the early course of the disease can occur as recurrent episodes lasting a few days or weeks, which over time, becomes persistently firm and indurated 3 .…”
Section: Discussionmentioning
confidence: 99%
“…It is therefore no surprise that diseases which primarily affect other parts of the gut often involve the oral mucosa. Hulla and Escudier describe inflammatory bowel diseases and their oral manifestations in great detail, including epidemiology, oral manifestations, diagnosis and management. Crohn's disease and ulcerative colitis have significant oral manifestations which may be the first to appear: hence dentists may initiate the diagnostic process and are called upon for treatment in symptomatic cases.…”
Section: Inflammatory Bowel Diseases and Oral Mucosamentioning
confidence: 99%
“…It is not possible to distinguish between OFG and oral CD either clinically or histopathologically. However immunological differences are though reported (Freysdottir et al 2007 ; Zbar et al 2012 ), and recent findings showed that there may be similar phenotypic characteristics despite different genetic characteristics and a different composition of the inflammatory infiltrate (Gale et al 2014 ; Gale et al 2015 ; Hullah and Escudier 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…The aetiology of OFG and CD is still unknown, but studies indicate a multifactorial origin (Tilakaratne et al 2008 ; Grave et al 2009 ; Al-Hamad et al 2015 ; Gale et al 2015 ; Hullah and Escudier 2019 ). In OFG, allergy or hypersensitivity may be a causative factor, since both atopy and contact hypersensitivity are observed in several OFG patients (James et al 1986 ; Armstrong et al 1997 ; Wray et al 2000 ; Fitzpatrick et al 2011 ; Campbell et al 2013 ; Patel et al 2013 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation